Genetic, epigenetic and enviromental influencing factors on the regulation of precocious and delayed puberty - Faienza, Maria Felicia; Urbano, Flavia; Moscogiuri, Luigi Antonio; Chiarito, Mariangela; De Santis, Stefania; Giordano, Paola (Frontiers in Endocrinology, 2022)
The onset of pubertal development is regulated by a network of genes that activate the pulsatile secretion of gonadotropin releasing hormone (GnRH), and subsequently increase the circulating levels of pituitary gonadotropins that stimulate gonadal activity. Although the transition from pre-pubertal condition to puberty occurs physiologically in a delimited age-range, the onset of pubertal development can be anticipated or delayed due genetic and epigenetic variations or environmental conditions. Most of the genetic and epigenetic alterations concern key components of the hypothalamic-pituitary-gonadal (HPG) axis, such as genes encoding kisspeptin, GnRH, LH and FSH and their receptor. Recent data indicate a fundamental role of the epigenome in the regulation of critical genes in the hypothalamus and pituitary that could mediate the plasticity of pubertal timing. Identification of epigenetically regulated genes, such as Makorin ring finger 3 (MKRN3) and Delta-like 1 homologue (DLK1), respectively responsible for the repression and activation of pubertal development, provides additional evidence of how epigenetic variations affect pubertal timing. This review aims to address genetic, epigenetic, and environmental mechanisms which have been demonstrated to regulate precocious and delayed puberty.